Serial MR Imaging of Experimental Autoimmune Encephalomyelitis Induced by Human White Matter or by Chimeric Myelin-Basic and Proteolipid Protein in the Common Marmoset - Jordan, E. Kay; McFarland, Hugh I.; Lewis, Bobbi K.; Tresser, Nancy; Gates, Michael A.; Johnson, Michele; Lenardo, Michael; Matis, Louis A.; McFarland, Henry F.; Frank, Joseph A. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Experimental autoimmune encephalomyelitis (EAE) in the marmoset was monitored by serial MR imaging to determine correlates to the natural-history MR studies in multiple sclerosis (MS). The relationships of MR-revealed lesions to clinical status and histopathologic findings were also explored.METHODS: We induced EAE by subcutaneous inoculation in two marmosets by human white matter (HWM) and in seven marmosets by MP4 (a chimeric recombinant fusion protein of myelin-basic and proteolipid protein) in adjuvant along with intravenous inactivated pertussis vaccine to facilitate the disease process. The HWM-inoculated animals were induced with Freund’s adjuvant as the established model of marmoset EAE. The MP4-inoculated animals were induced with either Freund’s incomplete adjuvant or TiterMax as part of a preclinical treatment trial. MR imaging was performed at 1.5 T at baseline, and repeated at 1- to 2-week intervals for a period of up to 16 weeks in six EAE-induced marmosets, and intermittently for up to 70 weeks in three EAE-induced and two control marmosets. Proton density–(PD-) and T2-weighted, pre- and postgadopentetate dimeglumine enhancement, T1-weighted, and magnetization transfer (MT) images were obtained. The brains were prepared for histologic evaluation of lesion distribution and counts, characterization of lesions as demyelinating or inflammatory, and histopathologic scoring. The clinical, MR, and pathologic scoring were done on grading systems, and correlated for evaluation.RESULTS: White matter (WM) changes after EAE induction were observed first at 9 days in the HWM-induced animals and at 2.5 weeks in the MP4-induced animals, with subsequent week-to-week fluctuations on PD- and T2-weighted images. Contrast-enhancing lesions were not observed in all animals. MR-revealed WM lesions correlated to histopathologic analysis of EAE lesions, measuring from 0.5 mm to 1.5 mm. The lesion count and extent of demyelination was greater in the HWM-induced animals than in the MP4-induced animals. Some MR-revealed lesions correlated directly to clinical symptoms, but the majority of lesions were clinically silent.CONCLUSION: On MR images, lesions in the EAE marmoset model were confined to the WM, and their development, resolution, distribution, and enhancing characteristics fluctuated over the duration of the study. The dynamic presentation of MR-revealed lesions confirms the parallels between EAE in the marmoset and relapsing-remitting MS. Clinical symptoms alone were not representative of ongoing pathologic brain lesions. Therefore, serial MR imaging serves as a very important adjunct to clinical and histologic surveillance of the development of new and the persistence of existing brain lesions in this animal model of MS.